2013
DOI: 10.1002/emmm.201202078
|View full text |Cite
|
Sign up to set email alerts
|

GLI1 regulates a novel neuropilin‐2/α6β1 integrin based autocrine pathway that contributes to breast cancer initiation

Abstract: The characterization of cells with tumour initiating potential is significant for advancing our understanding of cancer and improving therapy. Aggressive, triple-negative breast cancers (TNBCs) are enriched for tumour-initiating cells (TICs). We investigated that hypothesis that VEGF receptors expressed on TNBC cells mediate autocrine signalling that contributes to tumour initiation. We discovered the VEGF receptor neuropilin-2 (NRP2) is expressed preferentially on TICs, involved in the genesis of TNBCs and ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
189
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 151 publications
(206 citation statements)
references
References 85 publications
14
189
1
Order By: Relevance
“…These pathways modulate GLI1 activity mainly via regulation of the expression of this transcription factor (1,(11)(12)(13)(14)(15)(16)(17)(18)(19)(20). Here, we provide evidence of a novel regulatory mechanism involving the interaction of components of the TGF␤ pathway (SMAD proteins) modulating GLI1 activity in cancer cells.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…These pathways modulate GLI1 activity mainly via regulation of the expression of this transcription factor (1,(11)(12)(13)(14)(15)(16)(17)(18)(19)(20). Here, we provide evidence of a novel regulatory mechanism involving the interaction of components of the TGF␤ pathway (SMAD proteins) modulating GLI1 activity in cancer cells.…”
Section: Discussionmentioning
confidence: 88%
“…These findings support the notion that increased expression of GLI1 is sufficient for the development of a subset of tumors. GLI1 activity is regulated by different oncogenic cascades, including the HEDGEHOG, EGFR, RAS, and TGF␤ pathways (1,(11)(12)(13)(14)(15)(16)(17)(18)(19)(20). It has been demonstrated that malignant transformation induced by some of these cascades requires an intact GLI1 transcriptional activity (17,20,21).…”
mentioning
confidence: 99%
“…In addition, CD49f cooperates with receptor tyrosine kinases to communicate, bidirectionally, between the cell and the extracellular matrix (ECM). Interestingly, however, the CD104 subunit appears to be expressed at very low levels, if at all in CSCs when compared to non-CSCs indicating that CD49fCD29 is the dominant integrin expressed by CSCs (81,82).…”
Section: Integrinsmentioning
confidence: 95%
“…Although the CD29/CD49f integrins have been implicated in the function of BCSCs and other CSCs (81,82,93), much needs to be learned about the contribution of these integrins to the genesis of BCSCs. It has been shown that CD49f and CD29 contribute to therapy resistance, tumor relapse and metastasis in breast cancer.…”
Section: Integrinsmentioning
confidence: 99%
“…To evaluate more rigorously the role of NRP-2 in the invasiveness of thyroid cancer cells following the activation of the VEGF-C/NRP-2 axis, an NRP-2 function-blocking antibody was used to selectively block the binding of the VEGF family ligands to NRP-2 (29,30). In NRP-2-overexpressing K1 cells, the VEGF-C/NRP-2 axis became defective due to the reduction in ERK and p38 MAPK phosphorylation (Fig.…”
Section: Vegf-c/nrp-2 Axis-mediated Migration and Invasion Of Thyroidmentioning
confidence: 99%